EVALUASI PROGRAM KELAS IBU HAMIL SEBAGAI UPAYA PERCEPATAN PENURUNAN STUNTING DI PUSKESMAS BESUKI, KABUPATEN SITUBONDO PADA TAHUN 2023 - Dinda Puspita; Suci Megawati (Publika, 2026)
This study aims to gain an in-depth understanding of the implementation and effectiveness of the Maternal Class Program as an effort to accelerate stunting reduction at Puskesmas Besuki, Situbondo Regency. The study employs a qualitative approach with a descriptive design, emphasizing the understanding of social context, behaviors, and the natural experiences of the research subjects. The research subjects include the Head of Puskesmas Besuki, Nutrition Program Coordinator, Village Midwives, and pregnant women with or with a history of Chronic Energy Deficiency (CED) and stunting. Informants were selected using purposive sampling until data saturation was reached. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, including data reduction, presentation, and conclusion drawing. Data validity was ensured through source and technique triangulation as well as member checking. The results indicate that the Maternal Class Program is effective in improving pregnant women’s knowledge and awareness of maternal health, nutrition, childbirth, and newborn care, and contributes to stunting prevention. The program is responsive to participants’ needs, on target, and successfully applies the principle of equitable service. However, program efficiency and adequacy need improvement, particularly in budget management, scheduling, and participant engagement. It is recommended to conduct regular budget evaluations, prepare transparent reports, improve schedule management, and adjust materials according to different pregnancy trimesters to optimize program effectiveness.